ISOLATION OF CYANIDE DEGRADING BACTERIA FROM GOLD-MINE TAILING - Mohamad Yani dan Dwi Meity Handayani (Department of Agroindustrial Technology, Bogor Agricultural University, 2011)
ABSTRACTThe isolation and identification of cyanide degrading bacteria conducted from the gold-mine tailing impoundment. The fresh tailing contained 0.81 – 2.17 ppm of CN and cyanide degrading bacteria populations. From fresh tailing sample, the cyanide degrading bacteria had been enriched using cyanide media which composed of 200 ppm of CN, 1-8 g/L of nutrient broth and trace element. By several times in enrichment culture, isolation and selection of single colonies which were formed on nutrient agar plates, several cyanide degrading bacteria were isolated successfully. Those bacteria were simplify identified by morphological and biochemical tests as Thiobacillus sp. The characteristics of Thiobacillus sp. were facultative anaerobic, rod shaped, motile, Gram negative, neutrophilic, and mesophilic. Thiobacillus B31P123 and B33P123 could utilize cyanide up to 500 ppm as its sole source of energy for growth. During the degradation of cyanide, ammonia was produced as the final products which slightly increased the pH of the medium Both isolates (B31P123 and B33P123) oxidized 200 ppm of CN which performed at rate of 0.32 and 0.35 ppm of CN/hr during logarithmic phase and produced ammonium up to 50 and 46 ppm, respectively. The nitrogen product was utilized at more than 80% for biomass cells growth.Keywords: cyanide, gold-mine-tailing, isolation, Thiobacillus